Evaluating the Satisfaction and Skills of Third Year Residents of Internal Medicine Ward in the Endoscopy Training Program Using Gastric Moulage Prepared in Sina Hospital Iran - Raika Jamali (Kerman University of Medical Sciences, 2015)
Background & Objective: Considering the possible risks of performing endoscopy training on patients the use of a moulage prior to training seems reasonable The aim of this study was to evaluate residents rate of satisfaction with the training process and their ability in performing upper gastrointestinal endoscopy using gastric moulage prepared in Sina Hospital Iran   Methods: This study was conducted on 20 residents of the endoscopy ward at Sina Hospital from September 2012 to September 2013 The endoscopy training program consisted of 3 steps of training with gastric moulage observation and training on human subjects The present educational development plan was evaluated through studying the 2 criteria of residents satisfaction and ability The satisfaction of residents with the endoscopy training course was evaluated by a selfreport questionnaire The residents ability in performing upper gastrointestinal endoscopy was evaluated by measuring the time of reaching the gastroesophageal junction and pyloric valve   Results: The reliability and validity of the selfreport questionnaire were 64% (060089) and 78% (012095) respectively Over 90% of residents agreed with the items of the selfreport questionnaire The highest rate of agreement belonged to the item that interpreted the effect of this method on lowering residents anxiety in performing endoscopy (100%) The mean ± standard deviation of time of reaching the gastroesophageal junction and pyloric valve were 1620 ± 1354 and 2728 ± 1375 seconds respectively   Conclusion: The results of this study showed that training residents using gastric moulage prepared in Sina Hospital was associated with residents satisfaction and the successful obtaining of the endoscopy skill